Bluestar's acquisition of Adisseo. B - McFarlan, F. Warren (Franklin Warren); Donghong, Li; Lei, Li ([London] : SAGE, 2016)
In early spring of 2013, Ren Jianxin, the General Manager of ChemChina and Chairman of Bluestar, was reading a brief report on the Nanjing Adisseo project. He was delighted that the Nanjing Adistar project had successfully passed acceptance tests and entered trial operation. It would be put into production in the middle of the year. It was already seven years since he led the Bluestar management team in acquiring the French Adisseo Company in January 2006. Many people inside and outside the industry had congratulated him at the time. During the following years, he and other executives of the company had worked hard to integrate and develop Adisseo.
Originally Published in: McFarlan, F.W., Donghong, L., & Lei, L. (2014). Bluestar's Acquisition of Adisseo (B). Beijing: Tsinghua SEM China Business Case Center.
Description based on online resource; title from home page (viewed on May 6, 2016).
Keywords: elektronické knihy; electronic books; Consolidation and merger of corporations -- Management -- Case studies